Heparin-induced thrombocytopenia: new insights into the immune response - Cosmi, Benilde (Translational Cancer Research; Vol 6, Supplement 1 (February 28, 2017): Translational Cancer Research, 2017)
Heparin induced thrombocytopenia (HIT) is an immuno mediated adverse reaction to heparin (both unfractionated and low molecular weight) due to the development of IgG antibodies against a self antigen, that is the complex of platelet factor 4 (PF4) and heparin or other polyanions. The IgG/heparin-PF4 immunocomplexes can cross-link with the Fcγ receptor IIa (FcγRIIa) on platelet surface. As a consequence, platelets are activated with intravascular aggregation and consumption, leading to thrombocytopenia. However, a paradoxical prothrombotic state ensues with coagulation activation and life-threatening venous and/or arterial thrombotic complications (1).